From Embassy Ties to Twitter Links: Comparing Offline and Online Diplomatic Networks. Issue 3 (20th February 2019) - Sevin, Efe; Manor, Ilan
Abstract : This article investigates how diplomatic networks move into a new digital media platform, namely Twitter, through the analytical lenses of networked diplomacy studies and mediatization. We employ the studies in the former field to argue for the need to study the entire network to evaluate diplomatic relations, rather than relying on bilateral relations alone. Mediatization is then introduced to argue that moving to a digital platform (i.e., digitization) is a process in which countries might end up enjoying different levels of technology adoption. We first use social network analysis to compare the sizes and structures of brick and mortar embassy networks and Twitter following–follower relationship networks among ministries and ministers of foreign affairs of 130 countries. We then present a theoretical explanation of digitization of diplomatic networks. Our findings suggest that the majority of countries still have a larger diplomatic presence offline compared to their Twitter network. However, the structures of offline and online networks are similar, showing that countries have diplomatic relations (whether brick and mortar embassies or Twitter links) with the same groups of countries. We conclude by presenting the variance of the digitization process among countries. Abstract : 摘要: 本文通过分析网络化外交研究和媒介化, 考察了外交网络如何进入推特这一新数字媒体平台。笔者运用以往的相关研究, 主张需研究整个网络来评价外交关系, 而不是仅依赖于双边关系。笔者随后引入了媒介化这一概念, 用于主张进入数字平台(即数字化)这一过程最终可能会使得国家采用不同层面的技术。笔者首先使用社会网络分析来比较130个国家外交部之间就使用大使馆网络和推特网络的规模和结构。笔者随后提出了外交网络数字化的理论解释。研究结果表明, 相比起使用推特网络, 大多数国家的外交依然更多地通过大使馆进行。然而, 线下和线上网络的结构是相似的, 这表明不论是通过大使馆还是通过推特, 各国都和与其相同的国家保持外交关系。笔者结论提出了各国间数字化进程的差异。 Abstract : Resumen: Las tecnologías de comunicación digital son ubicuas e influyen en casi todos los aspectos de la vida social, desde vidas de individuos hasta vidas de corporaciones multinacionales. Como era de esperar, los estados de las naciones no han estado exentos de los impactos de la digitalización, y tales tecnologías han mostrado su impacto en la diplomacia como un componente vital de las relaciones internacionales y los asuntos exteriores. Este artículo examina la digitalización de las redes diplomáticas mediante el uso de la mediatización como un marco analítico. Comparamos los tamaños y estructuras de las redes de embajadas reales y las redes de seguidores de Twitter entre los ministerios y ministros de asuntos exteriores de 130 países. Nuestros hallazgos resaltan la existencia de una red diplomática de Twitter, a pesar de su menor tamaño, y la varianza del proceso de digitalización entre países.